Representation of racial minorities in cardiac surgery randomized clinical trials. Issue 5 (2nd March 2022) - Cancelli, Gianmarco; Audisio, Katia; Perezgrovas‐Olaria, Roberto; Soletti, Giovanni J.; Chadow, David; Rahouma, Mohamed; Robinson, N. B.; Gaudino, Mario
Abstract: Background: Racial minorities account for 39.9% of the population in the United States, but are often underrepresented in clinical research. Results from studies predominantly enrolling White patients may not apply to racial minorities. The aim of this analysis is to assess the representation of racial minorities in cardiac surgery randomized clinical trials (RCTs). Methods: A systematic search of the literature was performed. All RCTs published from 2000 to 2020 including at least 100 patients and comparing two or more adult cardiac surgery procedures were included. Meta‐analytic estimates were calculated. Results: Among 51 cardiac surgery RCTs published between 2000 and 2020, only 9 (17.6%) reported the race of patients and were included in the final analysis. All of them were multicentric, with a mean of 33 centers included. Six RCTs enrolled patients undergoing coronary artery bypass grafting (66.7%), while the remaining three were on valve surgery (33.3%). Overall, 9193 patients were included; of them, 8034 (87.4%) were White and 1026 (11.2%) nonWhite (386 [4.2%] Black, 191 [2.1%] Hispanic, 274 [3.0%] from other races, and 175 [1.9%] nonWhite patients of unspecified race). The proportion of nonWhite patients did not change over time. Conclusions: Only 9 (17.6%) of the 51 cardiac surgery RCTs published between 2000 and 2020 reported the race of the patients enrolled and only 11.2% of them were nonWhite patients. Given the association between race and clinical outcomes, future RCTs should either guarantee a balanced inclusion of racial minorities or be designed to specifically enroll them.